Analysis Of Factors That Affect Audit Delay In Pharmaceutical Companies Listed On The Indonesia Stock Exchange - Armaya, Mei Linda (Indonesian Journal of Economics and Finance, 2024)
This research is a study conducted to determine the effect of KAP reputation, company size and audit opinion on audit delay in Pharmaceutical Companies listed on the Indonesia Stock Exchange for the 2018-2021 Period. This study uses a quantitative approach with secondary data sources obtained from the company's financial statements published at www.idx.co.id. The sampling technique in this study is to use purposive sampling technique, with the number of company objects with data for 4 years so that it has a total sample of 48 data. The analysis conducted in this study includes logistic regression model analysis with the software used to conduct this research is SPSS version 22.Based on the results of the study, it is concluded that KAP reputation has an effect on audit delay, company size has an effect on audit delay, audit opinion has no effect on audit delay. Then the reputation of KAP, company size and audit opinion together have no effect on Audit Delay.